Response of the nosZ-type denitrifying microbial community and metabolic characteristics to precipitation changes in the alpine wetland - Ni Zhang; Ni Zhang; Ni Zhang; Hongchen Jiang; Hongchen Jiang; Zhiyun Zhou; Zhiyun Zhou; Zhiyun Zhou; Yijun Wang; Desheng Qi; Desheng Qi; Desheng Qi; et al. (Frontiers in Microbiology)
The impact of climate change on the global hydrological cycle is becoming increasingly significant, with changes in precipitation patterns emerging as a key factor influencing the carbon and nitrogen cycling processes in alpine wetland ecosystems. However, the response of the nosZ-type denitrifying microbial community and its metabolic characteristics in the source wetland to precipitation changes remains unclear. In this study, high-throughput sequencing of the nosZ gene and LC-MS-based metabolomics were used to investigate the response of the nosZ-type denitrifying microbial community and its metabolic characteristics to precipitation changes (4 years) in the source wetland of Qinghai Lake. The results showed that Microvirga was the key bacterial group in the source wetland of Qinghai Lake, and Azospirillum was sensitive to changes in precipitation (P < 0.05). The 50% rainfall enhancement treatment significantly increased soil moisture, and the total carbon content showed an increasing trend with the increase in precipitation (P < 0.05). pH was the most important explanatory factor for community structure, while total nitrogen content was the key explanatory factor for community diversity. Deterministic processes dominated the assemblage of the nosZ-type denitrifying microbial community in the source wetland of Qinghai Lake. Soil metabolomics analysis showed that the differential metabolites in the Source Wetland mostly exhibited significant positive correlations. Precipitation changes significantly affected the relative abundance of N-Acetylaspartic acid. In summary, lower precipitation is more favorable for maintaining carbon storage in the source wetlands of Qinghai Lake. Precipitation variation disrupted the existing nitrogen balance within the ecosystem and altered the structure of the nosZ-type denitrifying microbial community and soil metabolic characteristics. These findings imply that climate change-driven shifts in precipitation patterns may impact carbon and nitrogen dynamics in alpine wetlands, alter ecosystem stability, and have profound effects on microbial communities and biogeochemical cycles.